1999
DOI: 10.2136/sssaj1999.03615995006300020012x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon, Nitrogen, and Aggregation in Response to Type and Frequency of Tillage

Abstract: Little information exists on the biogeochemical effects of combining no‐tillage planting with paraplowing (to improve deep water penetration) or with secondary tillage (to control weeds). We determined surface residue and soil C and N pools (total, particulate, microbial biomass, and mineralizable) and water‐stable aggregation at depths of 0 to 25, 25 to 75, and 75 to 150 mm from a Cecil sandy loam (fine, kaolinitic, thermic Typic Kanhapludults) in Georgia. Soil tillage treatments were a factorial arrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(92 citation statements)
references
References 0 publications
9
80
0
3
Order By: Relevance
“…The highest amount of organic matter was observed under NT. Franzluebbers et al (1999) observed that the concentration of organic matter was higher in the surface soil under no-tillage systems. Less disruption resulted in greater accumulation of surface residue carbon.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 93%
“…The highest amount of organic matter was observed under NT. Franzluebbers et al (1999) observed that the concentration of organic matter was higher in the surface soil under no-tillage systems. Less disruption resulted in greater accumulation of surface residue carbon.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 93%
“…Briefly, soil microbial biomass C was determined with chloroform fumigation-incubation without subtraction of a control and using an efficiency factor of 0.41 (Voroney and Paul, 1984;Franzluebbers et al, 1999). The flush of CO 2 following rewetting of dried soil (3 d) and cumulative C and N mineralization during 24 d of incubation were determined with aerobic incubation of soil at 50% water-filled pore space and 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…9). This more pronounced aggregation increase does, however, not seem to lead to an [3,26,[30][31][32]35,38,59,65,77,79,109,111,113,114,139,164,172,173,177,194,Paustian and Elliott,unpublished,214,219,220,241] for (sub)tropical soils and from [2,11,22,42,50,[54][55][56]58,67,72,78,84,85,89,93,95,96,104,105,133,134,136,146,…”
Section: Mechanisms Of C Sequestration Under No-tillagementioning
confidence: 99%
“…Relative soil aggregation under no-tillage (NT) versus conventional tillage (CT), expressed as the ratio of the mean weight diameter of water-stable aggregates. Data from [35,57,59,60,106,111,132,137,164,188,216,228] for (sub)tropical soils and from [8,53,108,115,161,233,250,264] for temperate soils. Table VII.…”
Section: Mechanisms Of C Sequestration Under No-tillagementioning
confidence: 99%